SKETSA DESAIN RUANGAN USAHA MIKRO KONVEKSI DI PASAR KLEWER SURAKARTA - Riyardi, Agung (WARTA, 2016)
The aim of the public servicing is to draw a simple design of Ar Ridho kiosk at Klewer traditional market, Surakarta city. This simple design is hoped as a basic in designing the kiosk that supports kiosk revenue increasing. The public servicing method used is a stakeholder and contingency approach assistancy method. The stakeholder approach is used in order to gain effectiveness in assistancy, while the contingency approach is used in order to gain more than one simple designs. The result is three pleasant, attractive and informative simple designs. All of simple designs have a similarity in describing a pleasant and attractive kiosk, but different in describing an informative kiosk. The pleasant and attractive kiosk is described by the vastness of kiosk. The first simple design describes an informative kiosk because provides an information computer, the second simple design describes a more informative kiosk because provides an information computer and mirror, and the third simple design describes an informative kiosk because provides an information computer, mirror and dressing room. Consummers respond the simple designs. Some responds suggest improvement into 2 or 3 simple design dimension and cost calculation for each simple design, while other responds suggest to the kiost such as room widening, display grouping and on-line transaction.